FORMULATION AND PHYSICAL STABILITY TEST OF GRISEOFULVIN MICROEMULSION GEL - Iradhati, Anindya Hana; Jufri, Mahdi (International Journal of Applied Pharmaceutics, 2017)
Objective: The main objective of this research is to make and evaluate the formulation of a griseofulvin microemulsion gel for topical use to increase the solubility and safety of the drug. Methods: The optimized microemulsion formula contains 5% oleic acid as the oil phase, 25% Tween 80 as the surfactant, and 20% ethanol (96%) as the cosurfactant. Results: Organoleptic observations of the microemulsion showed that it had a clear and transparent yellowish color, while the microemulsion gel had a hazy yellowish color. Both the microemulsion and the microemulsion gel had the smell of alcohol. The size of the globules in the microemulsion and the microemulsion gel was 158.0 nm and 226.0, respectively. Conclusions: The griseofulvin microemulsion gel was stable at 4°C±2°C, 25°C±2°C, and 40°C±2°C.